The influence of experimental conditions on absolute beam density measurements for NH 3 and H - Pandey, R; Wu, LY; Morris, L; Regan, P; Heazlewood, BR (Springer, 2024)
In order to establish important reaction properties, such as rate coefficients, it is often necessary to know the number of reactants that are present in an interaction region. The absolute number densities of pulsed supersonic molecular (NH3) and atomic (H) beams are reported using a laser-based detection method, under a range of experimental conditions including photolysis, Zeeman deceleration, and magnetic focusing. Time-averaged densities of (3.6 ± 2.7) × 104 cm-3 are reported for successfully Zeeman-decelerated and magnetically focused H atoms, generated by the photodissociation of precursor NH3 molecules. Without the magnetic guide components in the beamline, the density of the target radicals of interest is somewhat lower, at (2.5 ± 1.8) × 104 cm-3. The average density of the undecelerated H atom beam is approximately an order of magnitude higher (2.9 ± 1.9) × 105 cm-3, with the average density of the molecular ammonia beam over two orders of magnitude higher again (5.1 ± 2.9) × 107 cm-3. The average number densities measured for the two different species of interest in this work span more than three orders of magnitude. These findings highlight the need for accurate and precise experimental measurements of number densities—for each species of interest, under the appropriate experimental conditions—before doing absolute rate coefficient calculations.